2017
DOI: 10.1186/s12989-017-0234-0
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of PTPN6 exacerbates aluminum oxide nanoparticle-induced COPD-like lesions in mice through activation of STAT pathway

Abstract: BackgroundInhaled nanoparticles can deposit in the deep lung where they interact with pulmonary cells. Despite numerous studies on pulmonary nanotoxicity, detailed molecular mechanisms of specific nanomaterial-induced lung injury have yet to be identified.ResultsUsing whole-body dynamic inhalation model, we studied the interactions between aluminum oxide nanoparticles (Al2O3 NPs) and the pulmonary system in vivo. We found that seven-day-exposure to Al2O3 NPs resulted in emphysema and small airway remodeling in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Ni may come from fuels (Genchi et al 2020). Exposure to Al and Ni is proven to cause COPD-like effects (Li et al 2017) and pulmonary cancer (Genchi et al 2020). Moreover, high Fe serum concentration have been detected in COPD patients (Asker et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Ni may come from fuels (Genchi et al 2020). Exposure to Al and Ni is proven to cause COPD-like effects (Li et al 2017) and pulmonary cancer (Genchi et al 2020). Moreover, high Fe serum concentration have been detected in COPD patients (Asker et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Masubuchi et al confirmed that inhibition of apoptosis in lung tissue of COPD mice can significantly inhibit the reduction of transient potential in lung tissue and improve its symptoms [16] . Li et al found that reducing the apoptosis rate of COPD injured mice can significantly improve the autoimmune ability of mice and shorten the recovery period [17] . Sun et al reported that improving the apoptosis of pulmonary microvessels can significantly improve the COPD injury of patients and prevent the deterioration of lung tissue [4] .…”
Section: Resultsmentioning
confidence: 99%
“…Treating male rats orally with three successive doses of AlNPs (25 mg/kg), resulted in significant DNA damage (increase in tail intensity) in bone marrow cells . Li et al (2017) found that treatment of mice with AlNPs (0.4 or 2 mg/m 3 ) through inhalation for seven days resulted in emphysema and small airway remodeling in lungs, accompanied with enhanced inflammation and apoptosis. Exposure to AlNPs led to inhibition of protein tyrosine phosphatase, non-receptor type 6 (PTPN6) and phosphorylation of Signal transducer and activator of transcription 3 (STAT3), involved in the development of pulmonary inflammatory disease.…”
Section: Genotoxicity 51 In-vitromentioning
confidence: 98%